Placing Image and Practice in Tension: South Korean Nurses, Medical Pedagogy, and the Indiana University Bloomington Nursing Program, 1958–1962. Issue 4 (1st December 2017) - DiMoia, John P.
Abstract : In the aftermath of the Korean War (1950–53), the symbolic and material reconstruction of South Korea began, with much of the relief work assumed under the broad banner of the United Nations and its various affiliates and with a wide range of international aid and relief organizations participating. With this dramatic increase in the areas of new medical infrastructure, training, and pedagogy, it remains surprising that much of the scholarship to date has focused largely on medical practitioners and their contributions to a rebuilding nation, that is, the Korean domestic context almost exclusively, suggesting a strong degree of continuity with the past. For South Korean nurses, this period (1954 to early 1960s) would see a radical reconfiguring of their professional practice, along with that of doctors, and, more important, their patterns of movement, as international migration to the United States and Europe was enhanced by changes to immigration law in and following 1965. Even before this change, however, Korean nurses began traveling abroad for further education and professional development, with the Korean War opening up numerous opportunities consistent with such aims. To borrow the language of historian Young-Sun Hong, medical personnel were rapidly becoming mobilized as a critical part of a much larger "global humanitarian regime, " one consistent with the work of Catherine Cineza Choy on medical migration of Filipino nurses.